2021
DOI: 10.1038/s41370-021-00376-8
|View full text |Cite
|
Sign up to set email alerts
|

The size and culturability of patient-generated SARS-CoV-2 aerosol

Abstract: Background Aerosol transmission of COVID-19 is the subject of ongoing policy debate. Characterizing aerosol produced by people with COVID-19 is critical to understanding the role of aerosols in transmission. Objective We investigated the presence of virus in size-fractioned aerosols from six COVID-19 patients admitted into mixed acuity wards in April of 2020. Methods Size-fractionated aerosol samples and aerosol siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 34 publications
6
80
1
Order By: Relevance
“…The CDC has determined that airborne transmission of SARS-CoV-2 can occur in environments which include enclosed spaces, prolonged exposure, and inadequate ventilation [ 2 ], which raises questions as to prolonged contact in an aircraft cabin environment. While projectile droplet transmission, dominated by their own inertia, likely does not vary substantially from the unique circumstance of being on an aircraft, the aerosol exposure route for smaller droplets and evaporated droplet nuclei is dependent on the ventilation, environment, and exposure time [ 3 , 4 ]. A variety of research supports this conclusion, including sampling infectious virus in the air [ 4 , 5 ], and case studies suggesting aerosol transmission [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC has determined that airborne transmission of SARS-CoV-2 can occur in environments which include enclosed spaces, prolonged exposure, and inadequate ventilation [ 2 ], which raises questions as to prolonged contact in an aircraft cabin environment. While projectile droplet transmission, dominated by their own inertia, likely does not vary substantially from the unique circumstance of being on an aircraft, the aerosol exposure route for smaller droplets and evaporated droplet nuclei is dependent on the ventilation, environment, and exposure time [ 3 , 4 ]. A variety of research supports this conclusion, including sampling infectious virus in the air [ 4 , 5 ], and case studies suggesting aerosol transmission [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While projectile droplet transmission, dominated by their own inertia, likely does not vary substantially from the unique circumstance of being on an aircraft, the aerosol exposure route for smaller droplets and evaporated droplet nuclei is dependent on the ventilation, environment, and exposure time [ 3 , 4 ]. A variety of research supports this conclusion, including sampling infectious virus in the air [ 4 , 5 ], and case studies suggesting aerosol transmission [ 6 8 ]. An example of the latter occurred in a poorly ventilated nursing home unit where 81% of patients and 50% of staff became infected.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Santarpia et al [ 44 ] also demonstrated the presence of infectious SARS-CoV-2 in aerosol samples. Using a NIOSH BC25 sampler the authors collected aerosols samples in five patient rooms in two different hospital wards; the samples were size-segregated in three groups: greater than 4.1 µm, 1–4 µm and less than 1 µm.…”
Section: Detection Of Sars-cov-2 In Air Samplesmentioning
confidence: 99%
“…Airborne transmission of SARS-CoV-2 is now widely accepted as a mode of transmission of SARS-CoV-2 [ 2 , 4 , 8 , 12 ]. This route dominates under certain environmental conditions, particularly indoor environments without proper ventilation [ 24 , 25 , 26 , 27 , 28 , 29 ], with a recent study demonstrating that some fraction of the RNA-containing aerosols emitted from infected people contain intact, replication-competent virions [ 30 ]. On the contrary, current evidence suggests that transmission through contaminated surfaces is rare; however, when it comes to healthcare settings where COVID-19 patients are being treated, especially in ICUs, aerosol-generating medical procedures take place which could potentially exacerbate the contamination of air and surfaces in the surrounding area [ 31 ].…”
Section: Discussionmentioning
confidence: 99%